Modified large crystalline USY zeolite for hydrocracking of hydrocarbon oils

By replacing the USY zeolite with a catalyst composition formed by combining specific elements, the existing catalysts are solved inefficient when dealing with high boiling point hydrocarbon materials, and more efficient decomposition of hydrogenated oil and removal of organic sulfur and nitrogen compounds is achieved, thereby improving the quality of hydrocarbon materials.

JP7625688B2Active Publication Date: 2025-02-03SAUDI ARABIAN OIL CO +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023512315
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2020-10-30
Publication Date
2025-02-03
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

The existing hydrogenated oil decomposition catalysts are inefficient when treating high-boiling point hydrocarbon materials, and are difficult to effectively remove organic sulfur and nitrogen compounds, affecting the quality of hydrocarbon materials.

Method used

Superstable Y-type (USY) zeolite is used for skeleton replacement, combined with elements such as titanium, zirconium or hafnium to form a catalyst composition with an average crystallite size of 5 μm to 50 μm, and the decomposition efficiency is improved by treating the hydrogenated oil under specific conditions.

Benefits of technology

It significantly improves the efficiency of the decomposition process of hydrogenated oil, enhances the decomposition ability of high-boiling point hydrocarbon materials, and effectively removes organic sulfur and nitrogen compounds, improving the quality of hydrocarbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625688000004
    Figure 0007625688000004
  • Figure 0007625688000005
    Figure 0007625688000005
  • Figure 0007625688000006
    Figure 0007625688000006
Patent Text Reader

Abstract

According to one or more embodiments of the present disclosure, a catalyst composition includes a catalyst support and at least one hydrogenation component disposed on the catalyst support. The catalyst support includes at least one USY zeolite having a framework substituted with titanium and / or zirconium and / or hafnium. The framework-substituted USY zeolite has an average crystallite size of 5 μm to 50 μm. Methods for making such catalysts and methods for using such catalysts in hydrocracking processes are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Description of Related Applications

[0001] This application claims priority to U.S. Patent Application No. 17 / 038,074, filed September 30, 2020, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to the hydrocracking of hydrocarbon oils, and more particularly to catalyst compositions for hydrocracking hydrocarbon oils, methods of making such catalyst compositions, and methods of using such catalyst compositions. [Background technology]

[0003] Hydrocracking processes are used commercially in numerous oil refineries to process a variety of hydrocarbon feeds that boil in the range of 370°C to 520°C in conventional hydrocracking units and above 520°C in residue hydrocracking units. In general, hydrocracking processes split the molecules of the hydrocarbon feed into smaller, i.e., lighter, molecules that have higher average volatility and economic value. In addition, hydrocracking processes typically improve the quality of the hydrocarbon feedstock by increasing the hydrogen-to-carbon ratio and removing organosulfur and organonitrogen compounds. The hydrocracking catalyst is a key feature of hydrocracking process technology.

[0004] Two types of catalysts are used in hydrocracking: pretreatment catalysts and cracking catalysts. Pretreatment catalysts are designed to remove contaminants such as sulfur and nitrogen from heavy hydrocarbon oils. Cracking catalysts are designed to split low-value heavy molecules into high-value transportation fuels. Cracking catalysts typically consist of active phase metals for hydrogenation, an amorphous support as a binder, and a zeolite as the cracking component. The active phase metals typically include nickel, molybdenum, and tungsten. An exemplary zeolite is ultrastable Y-type zeolite (USY zeolite). Summary of the Invention [Problem to be solved by the invention]

[0005] There is a continuing need for more effective hydrocracking catalyst compositions. [Means for solving the problem]

[0006] It has now been discovered that a catalyst composition comprising at least one ultrastable Y-type (hereinafter "USY") zeolite framework-substituted with titanium, zirconium, hafnium, or a combination of two or more thereof and having an average crystallite size of 5 μm to 50 μm can significantly improve the effectiveness of a hydrocracking process.

[0007] According to one embodiment, the catalyst composition comprises at least one hydrogenation metal component and a support, the support comprising a framework-substituted ultrastable Y-type (USY) zeolite substituted with zirconium, titanium, or both zirconium and titanium atoms, the framework-substituted USY zeolite having an average crystallite size of 5 μm to 50 μm.

[0008] According to one embodiment, a method of making a catalyst composition includes forming an ultrastable Y-type (USY) zeolite having an average crystallite size of 5 μm to 50 μm; heating the USY zeolite at a temperature of 500° C. to 700° C.; forming a suspension comprising the USY zeolite and having a liquid / solid ratio of 5 to 15; adding at least one inorganic acid, at least one organic acid, or a mixture of at least one inorganic acid and at least one organic acid to the suspension such that the pH of the suspension is 2 or less; mixing a zirconium compound, a titanium compound, a hafnium compound, or a mixture of two or more thereof with the suspension having a pH of 2 or less; and adding a base such that the pH of the suspension is 6 to 8 to provide a framework-substituted USY zeolite.

[0009] According to one embodiment, a method for hydrocracking a hydrocarbon oil comprises contacting the hydrocarbon oil with at least one catalyst composition and hydrogen in a reactor to hydrocrack the hydrocarbon oil. The catalyst composition comprises at least one hydrogenation metal component and a support. The support comprises a framework-substituted ultrastable Y-type (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms. The framework-substituted USY zeolite has an average crystallite size of 5 μm to 50 μm.

[0010] Additional features and advantages of the embodiments described herein are set forth in the detailed description which follows, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the detailed description and claims provided below. [Brief description of the drawings]

[0011] The following detailed description of specific embodiments of the present disclosure can be best understood when read in conjunction with the following drawings. [Figure 1] SEM image of conventional sized NaY zeolite at 10,000x magnification [Diagram 2] 1 shows an SEM image of large crystal NaY zeolite at 10,000x magnification according to one or more embodiments of the present disclosure. [Diagram 3] SEM image of conventional sized NaY zeolite at 30,000x magnification [Figure 4] 1 shows an SEM image of large crystal NaY zeolite at 30,000x magnification according to one or more embodiments of the present disclosure. [Diagram 5] Crystallite size distribution curves of conventionally sized and large crystallized NaY zeolites. [Figure 6] Chart of VGO feed conversion vs. reactor temperature [Figure 7] Chart of Middle Distillate (MD) and Naphtha Selectivity vs. VGO Feed Conversion DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In an embodiment, the catalyst composition comprises a catalyst support and at least one hydrogenation component disposed on the catalyst support. The catalyst support comprises at least one USY zeolite having a framework substituted with titanium and / or zirconium and / or hafnium (hereinafter "FS-USY zeolite"). The FS-USY zeolite has an average crystallite size of 5 μm to 50 μm. The embodiment will now be described in more detail.

[0013] As used herein, the term "hydrocarbon oil" or "hydrocarbon feedstock" refers to an oily liquid consisting mostly of a mixture of hydrocarbon compounds. Hydrocarbon oils may include crude oil, synthetic crude oil, bitumen, oil sands, shale oil, or refined oils obtained from petroleum. The term "refined oil" includes, but is not limited to, vacuum gas oil (VGO), deasphalted oil (DAO) obtained from a solvent deasphalting process, demetallized oil (DMO), light and / or heavy coker gas oil obtained from a coker process, cycle oil obtained from a fluid catalytic cracking (FCC) process, and gas oil obtained from a visbreaking process.

[0014] As used herein, the term "hydrocarbon" refers to a compound composed entirely of carbon and hydrogen atoms.

[0015] As used herein, the term "crystal lattice constant" refers to the physical dimensions of a unit cell within a crystal lattice. Crystal lattice constants can be determined according to ASTM D3942-03, entitled "Standard Test Method for Determination of the Unit Cell Dimension of a Faujasite-Type Zeolite," the entire contents of which are incorporated herein by reference.

[0016] As used herein, the term "specific surface area" refers to the total surface area of ​​a zeolite per unit mass. Specific surface area may be determined by ASTM D3663-03, entitled "Standard Test Method for Surface Area of ​​Catalysts and Catalyst Carriers," the entire contents of which are incorporated herein by reference. Alternatively, specific surface area may be determined using the Brunauer-Emmett-Teller ("BET") model. Alternatively, specific surface area may be determined by ASTM D4365-19, entitled "Standard Test Method for Determining Micropore Volume and Zeolite Area of ​​a Catalyst," the entire contents of which are incorporated herein by reference.

[0017] As used herein, the term "hydrogen / oil ratio" or "hydrogen to oil ratio" refers to a standard measure of the volumetric flow rate of hydrogen circulating through a reactor relative to the volume of feed. The hydrogen / oil ratio may be determined by comparing the flow rate of the hydrogen gas stream to the flow rate of the hydrocarbon feed using a standard flow meter.

[0018] As used herein, the term "liquid hourly space velocity" or "LHSV" refers to the ratio of the liquid flow rate of the hydrocarbon feed to the catalyst volume or mass.

[0019] As used herein, the term "catalytic activity" or "catalytic activity" refers to the increase in the rate of a hydrocracking process due to the presence of a catalyst and can be approximated as the temperature at which 50% of the feed is converted. The higher the catalytic activity, the lower such temperature.

[0020] In one embodiment, the catalyst composition may include a catalyst support and at least one hydrogenation component. In an embodiment, the catalyst composition may include 60% to 99.99% by weight of the support. For example, the catalyst composition may include 65% to 95% by weight, 60% to 90% by weight, 65% to 85% by weight, or even 70% to 80% by weight of the support. It should be understood that the catalyst composition may include the support in an amount ranging from any of the lower limits of such ranges described herein to any of the upper limits of such ranges described herein. In an embodiment, the catalyst composition may include 0.01% to 40% by weight of the hydrogenation component. For example, the catalyst composition may include 1% to 40% by weight, 5% to 35% by weight, 10% to 30% by weight, or even 15% to 25% by weight of the hydrogenation component. It should be understood that the catalyst composition may include the hydrogenation component in an amount ranging from any of the lower limits of such ranges described herein to any of the upper limits of such ranges described herein. Without intending to be bound by any particular theory, it is believed that if the amount of hydrogenation component in the catalyst composition is too high relative to the amount of support, the dispersion of the hydrogenation metals on the catalyst will not be optimal. For example, if the catalyst composition contains more than 40 wt. % of the hydrogenation component, the hydrogenation metals may agglomerate on the support.

[0021] The catalyst support may include at least one USY zeolite, which may have a framework substituted with titanium and / or zirconium and / or hafnium. In embodiments, the catalyst support may include 0.1% to 90% by weight of FS-USY zeolite. For example, the catalyst support may include 0.1% to 85%, 5% to 80%, 10% to 75%, 15% to 70%, 20% to 65%, 25% to 60%, 30% to 55%, 35% to 50%, or even 40% to 45% by weight of FS-USY zeolite. It should be understood that the catalyst support may include an amount of FS-USY zeolite within a range formed from any of the lower limits of such ranges described herein to any of the upper limits of such ranges described herein. Without intending to be bound by any particular theory, it is believed that an amount of zeolite in the catalyst support greater than 90% limits the formation of catalyst pellets / extrudates.

[0022] In an embodiment, framework substitution can be accomplished by a post-modification process in which the zeolite is dealuminated and subsequently incorporated with transition metals such as Ti and / or Zr and / or Hf. As a result, the titanium and / or zirconium and / or hafnium framework substituted zeolite will have a higher silica to alumina molar ratio (hereinafter "SAR") than the unsubstituted zeolite. Without intending to be bound by any particular theory, it is believed that this post-modification creates mesoporosity (as used herein, referring to having pores with diameters between 2 nm and 50 nm), thereby providing the zeolite with the ability to accommodate larger molecules within the pores. It is also believed that this post-modification process increases the number of medium strength acid sites while decreasing the number of strong acid sites, improving the dispersion of hydrogenation metals on the catalyst surface.

[0023] In an embodiment, the post-modification of USY zeolite may be carried out by the following process: The zeolite may be placed in suspension such that the mass ratio of liquid to solid zeolite is between 5 and 15. An inorganic or organic acid may be added to the suspension such that the pH of the suspension is less than 2. At least one zirconium compound and / or at least one titanium compound and / or at least one hafnium compound may be added to the acidic suspension, which is then mixed and neutralized to ensure a post-modified catalyst. An exemplary process for preparing titanium and / or zirconium and / or hafnium substituted USY zeolite frameworks is described in U.S. Pat. No. 10,293,332, the entire contents of which are incorporated herein by reference. Framework substitution may be monitored, for example, by ultraviolet-visible-near infrared spectroscopy (UV-Vis-NIR or UV-vis), Fourier transform infrared spectroscopy (FT-IR), or nuclear magnetic resonance spectroscopy (NMR).

[0024] In embodiments, the USY zeolite may be independently substituted with 0.1% to 5% by weight zirconium and / or 0.1% to 5% by weight titanium and / or 0.1% to 5% by weight hafnium, calculated on an oxide basis. That is, in embodiments, one or more of zirconium, titanium, and hafnium may be absent, but at least one of zirconium, titanium, and hafnium may be present. For example, the USY zeolite may be substituted with only zirconium, only titanium, only hafnium, both zirconium and titanium, both zirconium and hafnium, both titanium and hafnium, or all three of zirconium, titanium, and hafnium.

[0025] In embodiments in which zirconium is present, the USY zeolite may contain 0.1 to 5% by weight zirconium, 0.5 to 4.5% by weight zirconium, 0.5 to 4% by weight zirconium, 0.5 to 3.5% by weight zirconium, 0.5 to 3% by weight zirconium, 0.5 to 2.5% by weight zirconium, 0.5 to 2% by weight zirconium, 0.5 to 1.5% by weight zirconium, 0.5 to 1% by weight zirconium, 1 to 4% by weight zirconium, 1 to 3.5% by weight zirconium, 1 to 3% by weight zirconium, 1 to 2.5% by weight zirconium, or even 1 to 2% by weight zirconium.

[0026] In the same or different embodiments, the USY zeolite may contain 0.5% to 4.5% by weight titanium, 0.5% to 4% by weight titanium, 0.5% to 3.5% by weight titanium, 0.5% to 3% by weight titanium, 0.5% to 2.5% by weight titanium, 0.5% to 2% by weight titanium, 0.5% to 1.5% by weight titanium, 0.5% to 1% by weight titanium, 1% to 4% by weight titanium, 1% to 3.5% by weight titanium, 1% to 3% by weight titanium, 1% to 2.5% by weight titanium, or even 1% to 2% by weight titanium.

[0027] In the same or a different embodiment, the USY zeolite may contain 0.5% to 4.5% by weight hafnium, 0.5% to 4% by weight hafnium, 0.5% to 3.5% by weight hafnium, 0.5% to 3% by weight hafnium, 0.5% to 2.5% by weight hafnium, 0.5% to 2% by weight hafnium, 0.5% to 1.5% by weight hafnium, 0.5% to 1% by weight hafnium, 1% to 4% by weight hafnium, 1% to 3.5% by weight hafnium, 1% to 3% by weight hafnium, 1% to 2.5% by weight hafnium, or even 1% to 2% by weight hafnium.

[0028] It should be understood that any amount of zirconium substitution described herein may be used with any amount of titanium substitution described herein and any amount of hafnium substitution described herein, including 0% by weight of any one or two of zirconium, titanium, and hafnium. It should further be understood that the range of substitution of any of the zirconium substitution or or titanium substitution or hafnium intrasubstitution may be formed by any of the lower limits of such substitution described herein and any of the upper limits of such substitution described herein.

[0029] Without intending to be bound by any particular theory, it is believed that the addition of zirconium and / or titanium and / or hafnium compounds in amounts less than 0.1 wt % does not improve the solid acid properties of the zeolite, and conversely, the addition of zirconium and / or titanium and / or hafnium compounds in amounts greater than 5 wt % would not further improve the activity of the zeolite and would unnecessarily increase the cost of the resulting catalyst.

[0030] In an embodiment, the FS-USY zeolite may have a crystal lattice constant of 2.42 nm to 2.45 nm. For example, the crystal lattice constant of the FS-USY zeolite may be 2.42 nm to 2.449 nm, 2.42 nm to 2.448 nm, 2.42 nm to 2.447 nm, 2.42 nm to 2.446 nm, 2.42 nm to 2.445 nm, 2.42 nm to 2.444 nm, 2.42 nm to 2.443 nm, 2.42 nm to 2.442 nm, 2.42 nm to 2.441 nm, 2.42 nm to 2.44 nm, 2.42 nm to 2.439 nm, 2.42 nm to 2.438 nm, 2.42 nm to 2.437 nm, 2.42 nm to 2.436 nm, 2.42 nm to 2.445 nm, 2.42 nm to 2.449 nm, 2.42 nm to 2.448 nm, 2.42 nm to 2.447 nm, 2.42 nm to 2.446 nm, 2.42 nm to 2.445 nm, 2.42 nm to 2.444 nm, 2.42 nm to 2.443 nm, 2.42 nm to 2.442 nm, 2.42 nm to 2.441 nm, 2.42 nm to 2.444 nm, 2.42 nm to 2.439 nm, 2.42 nm to 2.438 nm, 2.42 nm to 2.437 nm, 2.42 nm to 2.436 nm, 2.42 nm to 2.445 nm, 435nm, 2.421nm to 2.45nm, 2.422nm to 2.45nm, 2.423nm to 2.45nm, 2.424nm to 2.45nm, 2.425nm to 2.45nm, 2.426nm to 2.45nm, 2.427nm to 2.45nm, 2.428nm to 2.45nm, 2.429nm to 2.45nm, 2.43nm to 2.45nm, 2.431nm to 2.45nm, 2.432nm to 2.45nm, 2.433nm to 2.45nm, 2.434nm to 2.45nm, or even 2.435nm to 2.45nm. It should be understood that the crystal lattice constant of the FS-USY zeolite may be in a range formed from any one of the lower limits of such crystal lattice constant described herein to any one of the upper limits of such crystal lattice constant described herein.

[0031] Without intending to be bound by any particular theory, it is believed that a crystal lattice parameter of FS-USY zeolite less than 2.42 nm would reduce the activity of the final hydrocracking catalyst. Such a reduction is due to the high SiO 2 / Al 2 O 3It is believed that this is the result of the molar ratio and the low number of solid acid sites that act as active sites for cracking hydrocarbons. On the contrary, the crystal lattice constant of FS-USY zeolite that is greater than 2.45 nm may destroy the crystal structure of FS-USY zeolite during hydrocracking reaction due to the low thermal resistance of FS-USY zeolite. If the crystal structure of FS-USY zeolite is destroyed, the activity of the hydrocracking catalyst composition that is finally formed will be reduced.

[0032] In one embodiment, the FS-USY zeolite is 600m 2 / g to 900m 2 / g. For example, the specific surface area of ​​FS-USY zeolite is 600 m 2 / g to 890m 2 / g, 600m 2 / g to 880m 2 / g, 600m 2 / g to 870m 2 / g, 600m 2 / g to 860m 2 / g, 600m 2 / g to 850m 2 / g, 600m 2 / g to 840m 2 / g, 600m 2 / g to 830m 2 / g, 600m 2 / g to 820m 2 / g, 600m 2 / g to 810m 2 / g, 600m 2 / g to 800m 2 / g, 610m 2 / g to 900m 2 / g, 620m 2 / g to 900m 2 / g, 630m 2 / g to 900m 2 / g, 640m 2 / g to 900m 2 / g, 650m 2 / g to 900m 2 / g, 660m 2 / g to 900m 2 / g, 670m 2 / g to 900m 2 / g, 680m 2 / g to 900m 2 / g, 690m 2 / g to 900m 2 / g, or even 700m 2 / g to 900m 2 / g. It should be understood that the specific surface area of ​​the FS-USY zeolite may be within a range formed from any one of the lower limits of such specific surface area described herein to any one of the upper limits of such specific surface area described herein. Without intending to be bound by any particular theory, it is believed that the specific surface area of ​​the FS-USY zeolite may be within a range formed from any one of the lower limits of such specific surface area described herein to any one of the upper limits of such specific surface area described herein. 2 It is believed that a specific surface area of ​​FS-USY zeolite less than 1000 nm / g would reduce the number of available solid acid sites, thereby reducing the catalytic activity of the resulting hydrocracking catalyst composition to an insufficient level.

[0033] In an embodiment, the catalyst composition comprising FS-USY zeolite is 200 ml 2 / g to 450m 2 For example, the specific surface area of ​​a catalyst composition containing FS-USY zeolite may be 210 m 2 / g to 450m 2 / g, 220m 2 / g to 450m 2 / g, 230m 2 / g to 450m 2 / g, 240m 2 / g to 450m 2 / g, 250m 2 / g to 450m 2 / g, 200m 2 / g to 440m 2 / g, 200m 2 / g to 430m 2 / g, 200m 2 / g to 420m 2 / g, 200m 2 / g to 410m 2 / g, or even 200m 2 / g to 400m 2 / g. It should be understood that the specific surface area of ​​the catalyst composition comprising the FS-USY zeolite may be within a range formed from any one of the lower limits of such specific surface area described herein to any one of the upper limits of such specific surface area described herein. Without intending to be bound by any particular theory, it is believed that the hydrocracking rate increases with increasing specific surface area from a specific surface area of ​​200 m 2 / g, the yield of middle distillates is thought to decrease. 2 Above 100 / g, the rate of hydrocracking may become too fast and product selectivities may be undesirably altered.

[0034] In an embodiment, the FS-USY zeolite has an SiO content of 5 to 100. 2 Against Al 2 O 3For example, the FS-USY zeolite may have a molar ratio of 5 to 99, 5 to 98, 5 to 97, 5 to 96, 5 to 95, 5 to 94, 5 to 93, 5 to 92, 5 to 91, 5 to 90, 5 to 89, 5 to 88, 5 to 87, 5 to 86, 5 to 85, 5 to 84, 5 to 83, 5 to 82, 5 to 81, 5 to 80, 5 to 79, 5 to 78, 5 to 77, 5 to 76, 5 to 75, 5 to 74, 5 to 73, 5 to 72, 5 to 71, 5 to 70, 5 to 69, 5 to 68, 5 to 67, 5 to 66, 5 to 65, 5 to 64, 5 to 63, 5 to 62, 5 to 61, 5 to 60, 5 to 59, 5 to 58, 5 to 57, 5 to 56, 5 to 55, 5 to 54, 5 to 53, 5 to 52, 5 to 51, 5 to 50, 5 to 49, 5 to 48, 5 to 47, 5 to 46, 5 to 45, 5 to 44, 5 to 43, 5 to 42, 5 to 41, 5 to 40, 6 to 100, 7 to 100, 8 to 100, 9 to 100, 10 to 100, 11 to 100, 12 to 100, 13 to 100, 14 to 100, 15 to 100, 16 to 100, 17 to 100, 18 to 100, 19 to 100, 20 to 100, 21 to 100, 22 to 100, 23 to 100, 24 to 100, 25 to 100, 26 to 100, 27 to 100, 28 to 100 , 29 to 100, 30 to 100, 31 to 100, 32 to 100, 33 to 100, 34 to 100, 35 to 100, 36 to 100, 37 to 100, 38 to 100, 39 to 100, 40 to 100, 41 to 100, 42 to 100, 43 to 100, 44 to 100, 45 to 100, 46 to 100, 47 to 100, 48 to 100, 49 to 100, or even 50 to 100 SiO 2 Against Al 2 O 3 The SiO molar ratio of FS-USY zeolite may be 2 Against Al 2 O 3 It should be understood that the molar ratio of can be within a range formed from any one of the lower such ratio limits described herein to any one of the upper such ratio limits described herein.

[0035] Without intending to be bound by any particular theory, it is believed that a silica-alumina molar ratio of FS-USY zeolite less than 5 may have high acid sites with high acid strength, and therefore the activity of the final hydrocracking catalyst in hydrogenation and hydrocracking tends to be reduced. In addition, a higher alumina content is associated with a lower stability of FS-USY. Conversely, a silica-alumina molar ratio of FS-USY zeolite greater than 100 will result in a lower hydrocracking activity in the cracking reactor of the final hydrocracking catalyst due to a lower number of solid acid sites effective for hydrocracking.

[0036] In an embodiment, the catalyst composition including the FS-USY zeolite may include a plurality of pores having a diameter of 600 Å or less. These pores having a diameter of 600 Å or less may have a volume of 0.4 ml / g to 0.75 ml / g. For example, the pore volume may be 0.4 ml / g to 0.74 ml / g, 0.4 ml / g to 0.73 ml / g, 0.4 ml / g to 0.72 ml / g, 0.4 ml / g to 0.71 ml / g, 0.4 ml / g to 0.7 ml / g, 0.4 ml / g to 0.69 ml / g, 0.4 ml / g to 0.68 ml / g, 0.4 ml / g to 0.67 ml / g, 0.4 ml / g to 0.66 ml / g, 0.4 ml / g to 0.65 ml / g, 0.41 ml / g, 0.4 ml / g to 0.68 ...8 ml / g, 0.4 ml / g to 0.68 ml / g, 0.4 ml / g to 0.68 ml / g, 0.4 ml / g to 0.68 ml / g, 0.4 ml / g to 0.68 ml / g, 0.4 ml / g to 0.68 ml / g, 0.4 ml / g to 0.68 ml / g, to 0.75 ml / g, 0.42 ml / g to 0.75 ml / g, 0.43 ml / g to 0.75 ml / g, 0.44 ml / g to 0.75 ml / g, 0.45 ml / g to 0.75 ml / g, 0.46 ml / g to 0.75 ml / g, 0.47 ml / g to 0.75 ml / g, 0.48 ml / g to 0.75 ml / g, 0.49 ml / g to 0.75 ml / g, or even 0.5 ml / g to 0.75 ml / g. It should be understood that the pore volume of the pores of the catalyst composition comprising the FS-USY zeolite having a diameter of 600 Å or less may be within a range formed from any one of the lower limits of such pore volume described herein to any one of the upper limits of such pore volume described herein.

[0037] Without intending to be bound by any particular theory, it is believed that when the pore volume is less than 0.40 ml / g, the specific surface area decreases. As a result, the activity of the hydrocracking catalyst and the yield of middle distillates decrease. Conversely, when the pore volume is greater than 0.75 ml / g, the specific surface area increases. As a result, the hydrocracking rate and product selectivity may be adversely altered.

[0038] In embodiments, the catalyst composition may include other additives. For example, the catalyst composition may include one or more inorganic oxides in addition to the zeolite described above. The inorganic oxide may function as a granulating agent or binder. Exemplary inorganic oxides include, but are not limited to, alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, and silica-alumina-zirconia.

[0039] In embodiments, one or more inorganic oxides may be a component of the catalyst support. In embodiments having both FS-USY zeolite and inorganic oxide, the FS-USY zeolite present may comprise 1% to 90%, 1% to 85%, 1% to 80%, 10% to 75%, 20% to 70%, or even 30% to 60% by weight of the support. In such embodiments, the inorganic oxide content may comprise 99% to 10%, 99% to 15%, 99% to 20%, 90% to 25%, 80% to 30%, or even 70% to 40% by weight of the support. It should be understood that the FS-USY zeolite may be present within a range formed from any one of the lower limits of such concentration described herein to any one of the upper limits of such concentration described herein. It should further be understood that the inorganic oxide may be present within a range formed from any one of the lower limits of such concentration described herein to any one of the upper limits of such concentration described herein. Without intending to be bound by any particular theory, it is believed that the catalyst will not have sufficient mechanical strength if the inorganic oxide content is below 10 wt. %. It is further believed that the catalyst will not have sufficient cracking ability if the zeolite content is below 1 wt. %.

[0040] A sample of zeolite will have a distribution of crystallite sizes with a peak concentration of one crystallite size. As used herein, the term "average crystallite size" refers to the most probable crystallite size in a sample of zeolite. For example, FIG. 5, described more fully in the Examples below, provides crystallite size distributions for both conventionally sized FS-USY zeolite and large crystalline FS-USY zeolite. Conventionally sized FS-USY zeolite typically has an average crystallite size of about 2 μm, as can be seen from the size distribution curve (a). However, as can be seen from the size distribution curve (b), the FS-USY zeolites described herein have a size distribution of 5 μm to 50 μm, 6 μm to 50 μm, 7 μm to 50 μm, 8 μm to 50 μm, 9 μm to 50 μm, 10 μm to 50 μm, 11 μm to 50 μm, 12 μm to 50 μm, 13 μm to 50 μm, 14 μm to 50 μm, 15 μm to 50 μm, 16 μm to 50 μm, 17 μm to 50 μm, 18 μm to 50 μm, 19 μm to 50 μm, 20 μm to 50 μm, 21 μm to 50 μm, 22 μm to 50 μm, 23 μm to 50 μm, 24 μm to 50 μm, 25 μm to 50 μm, 26 μm to 50 μm, 27 μm to 50 μm, 28 μm to 50 μm, 29 μm to 50 μm, 30 μm to 50 μm, 31 μm to 50 μm, 32 μm to 50 μm, 33 μm to 50 μm, 34 μm to 50 μm, 35 μm to 50 μm, 36 μm to 50 μm, 37 μm to 50 μm, 38 μm to 50 μm, 39 μm to 50 μm, 40 μm to 50 μm, 41 μm to 50 μm, 42 μm to 50 μm, 43 μm to 50 μm, 44 μm to 50 μm, 45 μm 6μm to 50μm, 17μm to 50μm, 18μm to 50μm, 19μm to 50μm, 20μm to 50μm, 21μm to 50μm, 22μm to 50μm, 23μm to 50μm, 24μm to 50μm, 25μm to 50μm, 26μm to 50μm, 27μm to 50μm, 28μm to 50μm, 29μm to 50μm, 30μm to 50μm, 5μm to 49μm, 5μm to 48μm, 5μm to 47μm, 5μm to 46μm, 5μm to 45μm, 5μm to 44μm, 5μm to 43μm, 5μm to 42μm, 5μm to 41μm, 5μm to 40μm, 5μm to 39μm, 5μm to 38μm, 5μm to 37μm, 5μm to 36μm, 5μm to 35μm, 5μm to 34μm, 5μm to In some embodiments, the crystallite size may be from 10 to 33 μm, 5 μm to 32 μm, 5 μm to 31 μm, 5 μm to 30 μm, 5 μm to 29 μm, 5 μm to 28 μm, 5 μm to 27 μm, 5 μm to 26 μm, 5 μm to 25 μm, 10 μm to 20 μm, 11 μm to 19 μm, 12 μm to 18 μm, 13 μm to 17 μm, or even 14 μm to 16 μm.It should be understood that the average crystallite size may fall within a range formed from any one of the lower limits of such average crystallite size described herein to any one of the upper limits of such average crystallite size described herein.

[0041] While not intending to be bound by any particular theory, it is believed that the larger average crystallite size of the zeolite used in the hydrocracking catalyst blend will result in higher catalyst activity and higher naphtha selectivity when compared to catalyst compositions using conventionally sized zeolites. Again, without intending to be bound by any particular theory, it is believed that the larger crystallite size increases the residence time of the hydrocarbons within the supercage formed by the zeolite, which in turn results in more extensive cracking.

[0042] In embodiments, the hydrogenation metal components may include metal components known for use in conventional hydrocracking catalysts, including, but not limited to, metal components from the long group 8 of the periodic table (iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum or gold) and / or metal components from group 6 (chromium, molybdenum or tungsten). For example, the hydrogenation metal components may include metal components from the platinum group (platinum, rhodium, palladium, etc.), or combinations of molybdenum or tungsten from group 6 with cobalt or nickel from group 8.

[0043] In another embodiment, a method for producing a catalyst composition includes forming a USY zeolite having an average crystallite size of 5 μm to 50 μm, heating the USY zeolite in a furnace having a temperature of 500° C. to 700° C., forming a suspension of the thus calcined USY zeolite at a pH of less than 2.0, mixing a zirconium compound and / or a titanium compound and / or a hafnium compound with the USY zeolite, and neutralizing the resulting suspension to produce a FS-USY zeolite. The resulting catalyst composition is as previously described.

[0044] Y-type zeolite may be formed by any method. An exemplary, non-limiting method is described below. An alumina solution is prepared by combining sodium hydroxide with aluminum powder in water. Similarly, a silica solution is prepared by combining sodium hydroxide with colloidal silica. The alumina solution is added to the silica solution while mixing in an ice bath, then kept at room temperature for at least 24 hours.

[0045] In conventional synthesis methods, Y zeolite is recrystallized under conditions that provide a zeolite having an average crystallite size of about 2 μm. For example, conventional recrystallization is performed at 60° C. for two or more days. However, in accordance with embodiments described herein, Y zeolite can be produced with an average crystallite size of 5 μm to 50 μm, 6 μm to 50 μm, 7 μm to 50 μm, 8 μm to 50 μm, 9 μm to 50 μm, 10 μm to 50 μm, 11 μm to 50 μm, 12 μm to 50 μm, 13 μm to 50 μm, 14 μm to 50 μm, 15 μm to 50 μm, 16 μm to 50 μm, 17 μm to 50 μm, 18 μm to 50 μm, 19 μm to 50 μm, 20 μm to 50 μm, 21 μm to 50 μm, 22 μm to 50 μm, 23 μm to 50 μm, 24 μm to 50 μm, 25 μm to 50 μm, 26 μm to 50 μm, 27 μm to 50 μm, 28 μm to 50 μm, 29 μm to 50 μm, 30 μm to 50 μm, 31 μm to 50 μm, 32 μm to 50 μm, 33 μm to 50 μm, 34 μm to 50 μm, 35 μm to 50 μm, 36 μm to 50 μm, 37 μm to 50 μm, 38 μm to 50 μm, 39 μm to 50 μm, 40 μm to 50 μm, 7μm to 50μm, 18μm to 50μm, 19μm to 50μm, 20μm to 50μm, 21μm to 50μm, 22μm to 50μm, 23μm to 50μm, 24μm to 50μm, 25μm to 50μm, 26μm to 50μm, 27μm to 50μm, 28μm to 50μm, 29μm to 50μm, 30μm to 50μm, 5μm to 49μm, 5μm to 48μm, 5μm to 47μm, 5μm to 46μm, 5μm to 45μm, 5μm to 44μm, 5μm to 43μm, 5μm to 42μm, 5μm to 41μm, 5μm to 40μm, 5μm to 39μm, 5μm to 38μm, 5μm to 37μm, 5μm to 36μm, 5μm to 35μm, 5μm to 34μm, 5μm to 33μm, 5μ The zeolite is recrystallized under conditions that provide a zeolite having an average crystallite size of 5 μm to 32 μm, 5 μm to 30 μm, 5 μm to 29 μm, 5 μm to 28 μm, 5 μm to 27 μm, 5 μm to 26 μm, 5 μm to 25 μm, 10 μm to 20 μm, 11 μm to 19 μm, 12 μm to 18 μm, 13 μm to 17 μm, or even 14 μm to 16 μm. For example, Table 1 provides time and temperature conditions for obtaining average crystallite sizes of 5 μm and 50 μm.

[0046] [Table 1]

[0047] Detailed methods for preparing FS-USY zeolite from Y-type zeolite are given in US Pat. No. 10,293,332, the entire contents of which are incorporated herein by reference.

[0048] The Y-type zeolite synthesized by the conventional method is subjected to exchange of sodium ions with ammonium ions by conventional methods to obtain USY zeolite. For example, Y-type zeolite is dispersed in water to prepare a suspension, and ammonium sulfate is added thereto. The solid material is washed with water at a temperature of 40°C to 80°C, followed by washing with an aqueous solution of ammonium sulfate. The product is then washed again with water at a temperature of 40°C to 95°C, and dried at 100°C to 180°C for 30 minutes to obtain ammonium-exchanged Y-type zeolite. The hydrogen-type Y-type zeolite is then prepared by calcining the ammonium-exchanged Y-type zeolite at 500°C to 800°C for 10 minutes to 10 hours in a saturated steam atmosphere. This process can be repeated to increase the amount of ammonium contained in the Y-type zeolite. In this regard, the final ammonium ion exchange rate will be 90% or more.

[0049] To provide FS-USY zeolite, the USY zeolite prepared as described above is first calcined at 500°C to 700°C, for example, 550°C to 650°C, for 30 minutes to 10 hours. If the calcination temperature of the USY zeolite is lower than 500°C, the amount of zirconium atoms and / or titanium atoms and / or hafnium atoms incorporated in the framework replacement treatment in the subsequent step tends to be smaller than that in a process in which the calcination is performed at 500°C to 700°C. However, if the calcination temperature is higher than 700°C, the specific surface area of ​​the USY zeolite may be reduced, and the amount of zirconium atoms and / or titanium atoms and / or hafnium atoms incorporated in the framework replacement treatment in the subsequent step tends to be smaller than that in a process in which the calcination is performed at 500°C to 700°C. Calcination may be performed in various atmospheres, including, but not limited to, air.

[0050] The calcined USY zeolite can then be suspended in water having a temperature of about 20° C. to about 30° C. to form a USY zeolite suspension. The liquid / solids weight ratio of the suspension can range from 5 to 15. For example, the liquid / solids weight ratio can be from 8 to 12.

[0051] An inorganic or organic acid can then be added to the suspension to obtain an acidic USY zeolite suspension. Exemplary acids include, but are not limited to, sulfuric acid, nitric acid, hydrochloric acid, carboxylic acid, and combinations of two or more thereof. It may be convenient to use an acid to adjust the pH of the suspension to less than 2, for example, 1 to 2. It has been found that a pH in the above range can prevent precipitation when an aqueous solution of a zirconium compound and / or an aqueous solution of a titanium compound and / or an aqueous solution of a hafnium compound is mixed with the suspension for the framework replacement process described further below.

[0052] A solution containing zirconium and / or titanium and / or hafnium compounds can be added to the acidic suspension and mixed. The addition of zirconium and / or titanium and / or hafnium compounds can be done gradually, for example, dropwise. Mixing can be done for 3 to 5 hours at room temperature, i.e., about 25°C to about 35°C. The mixed solution can then be neutralized to a pH of 7 to 7.5 by adding a base, and dried at 80°C to 180°C to obtain FS-USY zeolite, in which zirconium and / or titanium and / or hafnium atoms form part of the zeolite framework by replacing aluminum atoms that were previously part of the zeolite framework. Exemplary bases include, but are not limited to, aqueous ammonia.

[0053] In embodiments, exemplary zirconium compounds include, but are not limited to, zirconium sulfate, zirconium nitrate, zirconium chloride, and combinations of two or more thereof. In embodiments, the amount of zirconium compound added may be 0.1% to 5% by weight based on zirconium oxide relative to the weight of the USY zeolite used. For example, 0.2% to 4% by weight of zirconium compound may be added. Adding an amount of zirconium compound less than 0.1% by weight may not achieve the desired USY zeolite properties. Adding an amount of zirconium compound greater than 5% by weight may clog the pores of the zeolite. In embodiments, an aqueous solution of zirconium compound prepared by dissolving zirconium compound in water may be used as the zirconium compound.

[0054] In embodiments, exemplary titanium compounds include, but are not limited to, titanium sulfate, titanium acetate, titanium chloride, titanium nitrate, titanium lactate, and combinations of two or more thereof. In embodiments, the amount of titanium compound added may be 0.1% to 5% by weight based on titanium oxide relative to the weight of the USY zeolite used. For example, 0.2% to 4% by weight of titanium compound may be added. Adding an amount of titanium compound less than 0.1% by weight may not achieve the desired USY zeolite properties. Adding an amount of titanium compound greater than 5% by weight may clog the pores of the zeolite. In embodiments, an aqueous solution of titanium compound prepared by dissolving titanium compound in water may be used as the titanium compound.

[0055] In embodiments, exemplary hafnium compounds include, but are not limited to, hafnium chloride, hafnium nitrate, hafnium fluoride, hafnium bromide, hafnium oxalate, and the like. In embodiments, the amount of hafnium compound added may be 0.1% to 5% by weight based on hafnium oxide relative to the weight of the USY zeolite used. For example, 0.2% to 4% by weight of hafnium compound may be added. Adding an amount of hafnium compound less than 0.1% by weight may not achieve the desired USY zeolite properties. Adding an amount of hafnium compound greater than 5% by weight may clog the zeolite pores and significantly increase the cost of the catalyst. In embodiments, an aqueous solution of a hafnium compound prepared by dissolving the hafnium compound in water is suitably used as the hafnium compound.

[0056] The FS-USY zeolite prepared as described above can then be impregnated by conventional methods with a hydrogenation metal component, which may, for example, include iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, or a combination of two or more thereof.

[0057] In another embodiment, a method for hydrocracking a hydrocarbon oil comprises contacting at least one hydrocarbon oil stream with at least one hydrocracking catalyst composition and hydrogen in a reactor to hydrocrack the hydrocarbon oil stream. The hydrocracking catalyst may be as described above. That is, the hydrocracking catalyst may comprise a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support may be 5 μm to 50 μm, 6 μm to 50 μm, 7 μm to 50 μm, 8 μm to 50 μm, 9 μm to 50 μm, 10 μm to 50 μm, 11 μm to 50 μm, 12 μm to 50 μm, 13 μm to 50 μm, 14 μm to 50 μm, 15 μm to 50 μm, 16 μm to 50 μm, 17 μm to 50 μm, 18 μm to 50 μm, 19μm to 50μm, 20μm to 50μm, 21μm to 50μm, 22μm to 50μm, 23μm to 50μm, 24μm to 50μm, 25μm to 50μm, 26μm to 50μm, 27μm to 50μm, 28μm to 50μm, 29μm to 50μm, 30μm to 50μm, 5μm to 49μm, 5μm to 48μm, 5μm to 4 7μm, 5μm to 46μm, 5μm to 45μm, 5μm to 44μm, 5μm to 43μm, 5μm to 42μm, 5μm to 41μm, 5μm to 40μm, 5μm to 39μm, 5μm to 38μm, 5μm to 37μm, 5μm to 36μm, 5μm to 35μm, 5μm to 34μm, 5μm to 33μm, 5μm to 32μm, 5μm to In some embodiments, the zeolite may include at least one FS-USY zeolite having an average crystallite size of from 10 μm to 30 μm, from 5 μm to 29 μm, from 5 μm to 28 μm, from 5 μm to 27 μm, from 5 μm to 26 μm, from 5 μm to 25 μm, from 10 μm to 20 μm, from 11 μm to 19 μm, from 12 μm to 18 μm, from 13 μm to 17 μm, or even from 14 μm to 16 μm.

[0058] The reactor may operate within a temperature range of 300° C. to 500° C. For example, the reactor may operate within a temperature range of 310° C. to 490° C., 320° C. to 480° C., 330° C. to 470° C., 340° C. to 460° C., 350° C. to 450° C., 360° C. to 440° C., 370° C. to 430° C., 380° C. to 420° C., 390° C. to 410° C., or even 395° C. to 405° C. It should be understood that the reactor may operate within a temperature range formed from any one of the lower such temperature limits described herein to any one of the upper such temperature limits described herein.

[0059] The hydrocarbon oil may have a boiling point of 375° C. to 833° C. For example, the hydrocarbon oil may have a boiling point of 400° C. to 800° C., 450° C. to 750° C., 500° C. to 700° C., 550° C. to 650° C., or even 575° C. to 625° C. It should be understood that the hydrocarbon oil may have a boiling point within a temperature range formed from any one of the lower such temperature limits described herein to any one of the upper such temperature limits described herein.

[0060] Hydrogen may be used to produce saturated hydrocarbons during the hydrocracking process. Hydrogen may be added to the reactor at pressures of 3.5 MPa to 25 MPa. For example, hydrogen may be added to the reactor at a pressure of from 4 MPa to 24.5 MPa, 4.5 MPa to 24 MPa, 5 MPa to 23.5 MPa, 5.5 MPa to 23 MPa, 6 MPa to 22.5 MPa, 6.5 MPa to 22 MPa, 7 MPa to 21.5 MPa, 7.5 MPa to 21 MPa, 8 MPa to 20.5 MPa, 8.5 MPa to 20 MPa, 9 MPa to 19.5 MPa, 9.5 MPa to 19 MPa, 10 MPa to 18.5 MPa, 10.5 MPa to 18 MPa, 11 MPa to 17.5 MPa, 11.5 MPa to 17 MPa, 12 MPa to 16.5 MPa, 12.5 MPa to 16 MPa, 13 MPa to 15.5 MPa, 13.5 MPa to 15 MPa, or even 14 MPa to 14.5 MPa. It should be understood that hydrogen may be added to the reactor within a range of pressures formed from any one of the lower such pressure limits described herein to any one of the upper such pressure limits described herein. Without intending to be bound by any particular theory, it is believed that process performance is significantly reduced at lower hydrogen pressures. Conversely, it is believed that processes using higher hydrogen pressures would require specialized equipment that would significantly increase the cost of the process.

[0061] The hydrogen feed and the hydrocarbon oil feed were fed in a manner that the hydrogen / oil ratio in the reactor was 500 normal cubic meters per cubic meter (hereafter referred to as "Nm 3 / m 3 ") to 2500Nm 3 / m 3 where the standard cubic meter is defined as the volume in cubic meters at standard temperature and pressure (15°C and 0.1 MPa). For example, the hydrogen / oil ratio is 550 Nm 3 / m 3 from 2450Nm 3 / m 3 , 600Nm 3 / m 3 from 2400Nm3 / m 3 , 650Nm 3 / m 3 from 2350Nm 3 / m 3 , 700Nm 3 / m 3 from 2300Nm 3 / m 3 , 750Nm 3 / m 3 from 2250Nm 3 / m 3 , 800Nm 3 / m 3 from 2200Nm 3 / m 3 , 850Nm 3 / m 3 from 2150Nm 3 / m 3 , 900Nm 3 / m 3 from 2100Nm 3 / m 3 , 950Nm 3 / m 3 from 2050Nm 3 / m 3 , 1000Nm 3 / m 3 from 2000Nm 3 / m 3 , 1050Nm 3 / m 3 from 1950Nm 3 / m 3 , 1100Nm 3 / m 3 from 1900Nm 3 / m 3 , 1150Nm 3 / m 3 from 1850Nm 3 / m 3 , 1200Nm 3 / m 3 from 1800Nm 3 / m 3 , 1250Nm 3 / m 3 from 1750Nm 3 / m 3 , 1300Nm 3 / m 3 from 1700Nm 3 / m3 , 1250Nm 3 / m 3 from 1650Nm 3 / m 3 , 1300Nm 3 / m 3 from 1500Nm 3 / m 3 , and even 1350Nm 3 / m 3 from 1450Nm 3 / m 3 It should be understood that the hydrogen / oil ratio may be within a range of ratios formed from any one of the lower limits of such ratios described herein to any one of the upper limits of such ratios described herein. Without intending to be bound by any particular theory, it is believed that process performance is significantly reduced at lower hydrogen / oil ratios. Conversely, it is believed that processes using high hydrogen / oil ratios would require specialized equipment that would significantly increase the cost of the process and increase gas holdup in the system, thereby reducing process performance.

[0062] The liquid hourly space velocity (hereinafter "LHSV") of the hydrocarbon feed in the reactor can be from 0.1 to 10 hours per hour. For example, the liquid hourly space velocity can be from 0.5 to 9.5 hours per hour, from 1 to 9 hours per hour, from 1.5 to 8.5 hours per hour, from 2 to 8 hours per hour, from 2.5 to 7.5 hours per hour, from 3 to 7 hours per hour, from 3.5 to 6.5 hours per hour, from 4 to 6 hours per hour, or even from 4.5 to 5.5 hours per hour. It should be understood that the LHSV can be within a range formed from any one of the lower LHSV limits described herein to any one of the upper LHSV limits described herein.

[0063] As previously mentioned, the hydrocracking process may be carried out in one or more reactors. Continuous flow reactors are well suited for this process, although the subject matter described herein is not so limited. Exemplary continuous flow reactors include, but are not limited to, stirred tank reactors, ebullated bed reactors, baffled slurry tanks, fixed bed reactors, rotating tubular reactors, slurry bed reactors, moving bed reactors, and combinations of two or more thereof.

[0064] According to one embodiment, either alone or in combination with any other embodiment, the catalyst composition comprises at least one hydrogenation metal component and a support. The support comprises a framework-substituted ultrastable Y-type (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms. The framework-substituted USY zeolite has an average crystallite size of 5 μm to 50 μm.

[0065] According to a second embodiment, either alone or in combination with any other embodiment, the framework-substituted ultrastable Y-zeolite is substituted with 0.1 to 5% by weight of zirconium atoms, calculated on the oxide basis.

[0066] According to a third aspect, either alone or in combination with any other aspect, the framework-substituted ultrastable Y-zeolite is substituted with 0.1 to 5% by weight of titanium atoms, calculated on the oxide basis.

[0067] According to a fourth aspect, either alone or in combination with the third aspect, the framework-substituted ultrastable Y-zeolite is substituted with 0.1 to 5% by mass, calculated on the oxide basis, of zirconium atoms.

[0068] According to a fifth aspect, either alone or in combination with any other aspect, the framework-substituted ultrastable Y zeolite comprises hafnium atoms.

[0069] According to a sixth aspect, either alone or in combination with the fifth aspect, the framework-substituted ultrastable Y-zeolite is further substituted with hafnium atoms.

[0070] According to a seventh embodiment, either alone or in combination with any other embodiment, the catalyst composition further comprises an inorganic oxide compound.

[0071] According to an eighth aspect, either alone or in combination with the seventh aspect, the inorganic oxide compound comprises alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, and combinations of two or more thereof.

[0072] According to a ninth embodiment, either alone or in combination with any other embodiment, the at least one hydrogenation metal component comprises from 0.01% to 40% by weight of the catalyst composition.

[0073] According to a tenth aspect, either alone or in combination with any other aspect, the framework-substituted ultrastable Y-type zeolite has a crystal lattice constant of 2.42 nm to 2.45 nm, a crystal lattice constant of 600 nm to 600 nm, 2 / g to 900m 2 / g, and 5 to 100 SiO 2 Against Al 2 O 3 The molar ratio is:

[0074] According to an eleventh aspect, either alone or in combination with any other aspect, the catalyst composition comprises 200 ml 2 / g to 450m 2 / g specific surface area and a plurality of pores having a diameter of 600 Å or less, the pores having a volume of 0.4 ml / g to 0.75 ml / g, and the at least one hydrogenation metal component comprises 0.01% to 40% by weight of the catalyst composition.

[0075] According to a twelfth embodiment, either alone or in combination with any other embodiment, the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

[0076] According to a thirteenth aspect, either alone or in combination with any other aspect, the framework substituted USY zeolite has an average crystallite size of from 10 μm to 20 μm.

[0077] According to a fourteenth embodiment, either alone or in combination with any other embodiment, the catalyst composition further comprises an inorganic oxide compound selected from the group consisting of alumina, silica, and mixtures of alumina and silica, and the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

[0078] According to a fifteenth embodiment, either alone or in combination with any other embodiment, a method of making a catalyst composition includes forming an ultrastable Y-type (USY) zeolite having an average crystallite size of 5 μm to 50 μm; heating the USY zeolite at a temperature of 500° C. to 700° C.; forming a suspension comprising the USY zeolite and having a liquid / solid ratio of 5 to 15; adding at least one inorganic acid, at least one organic acid, or a mixture of at least one inorganic acid and at least one organic acid to the suspension such that the pH of the suspension is 2 or less; mixing a zirconium compound, a titanium compound, a hafnium compound, or a mixture of two or more thereof with the suspension having a pH of 2 or less; and adding a base such that the pH of the suspension is 6 to 8 to provide a framework-substituted USY zeolite.

[0079] According to a sixteenth aspect, either alone or in combination with any other aspect, the ultrastable Y zeolite is obtained by the process described above, which has a crystal lattice constant of 2.42 nm to 2.45 nm, a crystal lattice constant of 600 nm to 600 nm, and a crystal lattice constant of 600 nm to 600 nm.2 / g to 900m 2 / g, and 5 to 100 SiO 2 Against Al 2 O 3 The molar ratio is:

[0080] According to a seventeenth embodiment, either alone or in combination with any other embodiment, the method further comprises adding at least one hydrogenation metal component to the catalyst composition.

[0081] According to an eighteenth embodiment, either alone or in combination with any other embodiment, the at least one hydrogenation metal component in the process is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

[0082] According to a nineteenth embodiment, either alone or in combination with any other embodiment, at least one hydrogenation metal component is added to the process such that the at least one hydrogenation metal component constitutes from 0.01% to 40% by weight of the catalyst composition.

[0083] According to a twentieth aspect, either alone or in combination with any other aspect, the framework substituted USY zeolite in the process has an average crystallite size of from 10 μm to 20 μm.

[0084] According to a twenty-first embodiment, either alone or in combination with any other embodiment, the method further comprises adding an inorganic oxide compound selected from the group consisting of alumina, silica, and mixtures of alumina and silica, and adding at least one hydrogenation metal component selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

[0085] According to a twenty-second embodiment, either alone or in combination with any other embodiment, a method for hydrocracking a hydrocarbon oil comprises contacting a hydrocarbon oil with at least one catalyst composition and hydrogen in a reactor to hydrocrack the hydrocarbon oil. The catalyst composition comprises at least one hydrogenation metal component and a support. The support comprises a framework-substituted ultrastable Y-type (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms. The framework-substituted USY zeolite has an average crystallite size of 5 μm to 50 μm.

[0086] According to a twenty-third embodiment, either alone or in combination with any other embodiment, the hydrocracking is carried out at a temperature of from 300° C. to 500° C.

[0087] According to a twenty-fourth aspect, either alone or in combination with any other aspect, the reactor is a continuous flow reactor, the hydrocarbon oil has a boiling point of 375°C to 833°C, hydrogen is added to the reactor at a pressure of 3.5MPa to 25MPa, the reactor has a liquid hourly space velocity of 0.1 hour to 10 hours, and the reactor is operated at a pressure of 500Nm 3 / m 3 from 2500Nm 3 / m 3 The hydrogen / oil ratio is

[0088] According to a twenty-fifth aspect, either alone or in combination with any other aspect, the method further comprises collecting a distillate from the reactor.

[0089] According to a twenty-sixth embodiment, either alone or in combination with any other embodiment, the reactor comprises a continuous flow reactor selected from the group consisting of a stirred tank reactor, an ebullated bed reactor, a baffled slurry tank, a fixed bed reactor, a moving bed reactor, a rotating tubular reactor, a slurry bed reactor, and combinations of two or more thereof.

[0090] According to a twenty-seventh aspect, either alone or in combination with any other aspect, the hydrocarbons include crude oil, synthetic crude oil, bitumen, oil sands, shale oil, refined oil obtained from petroleum, or a combination of two or more thereof.

[0091] According to a twenty-eighth embodiment, either alone or in combination with any other embodiment, the refined oil comprises vacuum gas oil, deasphalted oil, demetallized oil, light coker gas oil, heavy coker gas oil, cycle oil obtained from a fluid catalytic cracking process, gas oil obtained from a visbreaking process, or a combination of two or more thereof.

[0092] According to a twenty-ninth embodiment, either alone or in combination with any other embodiment, the framework-substituted USY zeolite has an average crystallite size of from 10 μm to 20 μm. EXAMPLES

[0093] Using the above described embodiments, exemplary catalyst compositions were prepared and characterized as follows.

[0094] Synthesis of Y-type zeolite Conventional size zeolite Y (NaY): An alumina solution was prepared by dissolving 10 g of NaOH in 20 g of double distilled water followed by the slow addition of 0.945 g of 99.5% pure aluminum powder. 50 g of colloidal silica (Ludox-HS, 30% by weight SiO 2 A silica solution was prepared by mixing 100 g of NaOH (pH=9.8) with 8.6 g of NaOH and 17 g of double distilled water. The container was placed in a 100° C. oven for 6 minutes. The alumina solution was added to the silica solution while mixing in an ice bath. The resulting mixture was kept at room temperature for 24 hours for aging. Crystallization was carried out at 60° C. for 1500 minutes to provide conventionally sized NaY zeolite, which will be used in the comparative examples below.

[0095] Large crystal Y-type zeolite: An alumina solution was prepared by dissolving 10 g of NaOH in 20 g of double distilled water followed by the slow addition of 0.945 g of 99.5% pure aluminum powder. 50 g of colloidal silica (Ludox-HS, 30% by weight SiO 2 A silica solution was prepared by mixing 8.6 g of NaOH (pH=9.8) with 17 g of double distilled water. The vessel was placed in a 100° C. oven for 6 minutes. The alumina solution was added to the silica solution while mixing in an ice bath. The resulting mixture was kept at room temperature for 24 hours for aging. Crystallization was carried out at 100° C. for 330 minutes to provide large crystal NaY zeolite.

[0096] Crystallite size measurement Scanning electron microscopy (SEM) images of conventional sized NaY zeolite and large crystal NaY zeolite were taken. Figure 1 shows an SEM image of conventional sized NaY zeolite at 10,000x magnification. Figure 2 shows an SEM image of large crystal NaY zeolite at 10,000x magnification. Figure 3 shows an SEM image of conventional sized NaY zeolite at 30,000x magnification. Figure 4 shows an SEM image of large crystal NaY zeolite at 30,000x magnification. Qualitatively, all figures showed a considerable difference in zeolite crystallite size between conventional sized NaY zeolite and large crystal NaY zeolite. Qualitatively, Figure 5 shows the crystallite size distribution curves of (a) conventional sized NaY zeolite and (b) large crystal NaY zeolite. Peak 1a of distribution curve (a) is at about 2 μm, while peak 1b of distribution curve (b) is at about 15 μm.

[0097] Post-modification of NaY zeolite Both the conventionally sized NaY zeolite and the large crystal NaY zeolite were then dealuminated as described in U.S. Pat. No. 10,293,332, the entire contents of which are incorporated herein by reference, and then post-modified by incorporating titanium and zirconium into the zeolite framework to provide conventionally sized titanium- and zirconium-framework substituted ultrastable Y-type ("TiZr-USY") zeolite and large crystal TiZr-USY zeolite, respectively.

[0098] First, NaY zeolite is subjected to exchange of sodium ions with ammonium ions by conventional methods. In one exemplary method, Y zeolite is dispersed in water to prepare a suspension, to which ammonium sulfate is added. The solid material is then washed with water, followed by washing with an aqueous solution of ammonium sulfate at a temperature of 40° C. to 80° C. The solid is then further washed with water at 40° C. to 95° C. and dried at 100° C. to 180° C. for 30 minutes, thus exchanging 50% to 70% of the sodium contained in the Y zeolite with NH 4 To produce ammonium exchanged Y-type zeolite,

[0099] Next, the ammonium-exchanged Y-zeolite is calcined at 500°C to 800°C for 10 minutes to 10 hours in a saturated steam atmosphere to prepare hydrogen-type Y-zeolite (HY). Next, the previously obtained HY zeolite is dispersed in water at 40°C to 95°C to prepare a suspension, to which ammonium sulfate is added, so that 80% to 97% of the sodium contained in the initial NaY zeolite is converted to NH 4 The suspension is stirred at 40°C to 95°C for 10 minutes to 3 hours. The solid material is then washed with water at 40°C to 95°C, followed by washing with an aqueous ammonium sulfate solution at 40°C to 95°C. The solid is then further washed with water at 40°C to 80°C and dried at 100°C to 180°C for 30 minutes to 30 hours. In this regard, the final ammonium ion exchange rate is at least 90%.

[0100] The ammonium exchanged Y zeolite thus obtained is calcined, for example, at 500° C. to 700° C. in a saturated steam atmosphere for 10 minutes to 10 hours to provide USY zeolite.

[0101] Next, the USY zeolite is subjected to a treatment for removing extra-skeletal aluminum (aluminum atoms not forming the zeolite framework). The extra-skeletal aluminum can be removed, for example, by dispersing the above-mentioned USY zeolite in warm water at 40°C to 95°C to prepare a suspension, adding sulfuric acid to the suspension, and stirring the suspension for 10 minutes to 3 hours while maintaining the temperature at 40°C to 95°C, thereby dissolving the extra-skeletal aluminum. After dissolving the extra-skeletal aluminum, the suspension is filtered, and the filter residue is washed with purified water at 40°C to 95°C and dried at 100°C to 180°C for 3 to 30 hours. In this way, USY zeolite from which extra-skeletal aluminum has been removed is obtained.

[0102] The USY zeolite from which the extra-framework aluminum has been removed is calcined at 500°C to 700°C for 30 minutes to 10 hours. The calcined ultrastable Y zeolite is suspended in water having a temperature of about 20°C to about 30°C to form a suspension having a liquid / solid mass ratio ranging from 5 to 15. An inorganic or organic acid is then added so that the pH of the suspension is less than 2, followed by gradually adding and mixing a solution containing a zirconium compound and a titanium compound. The mixed solution is then neutralized (pH 7.0 to 7.5) and dried at 80°C to 180°C, thus providing TiZr-USY zeolite.

[0103] Formulation of the Catalyst Composition Catalyst composition 1 (comparative) was formulated using 30 wt.% conventional sized TiZr-USY zeolite and 70 wt.% alumina only binder. Catalyst composition 2 (invention) was formulated using 30 wt.% large crystal TiZr-USY zeolite and 70 wt.% alumina only binder. This combined TiZr-USY zeolite and binder is referred to as the "support." Both catalyst composition 1 and catalyst composition 2 had 16 wt.% molybdenum trioxide and 4 wt.% nickel oxide, calculated as components of the support.

[0104] Pilot Plant Hydrocracking Process Both catalyst composition 1 and catalyst composition 2 were used in a hydrocracking process on a vacuum gas oil (VGO) feed. VGO has a catalytic activity of 0.9203 g / cm at 15°C. 3 The feed had a density of 1.08 kg / m2, a sulfur content of 2.231 wt%, and a nitrogen content of 815 ppm (wt). The initial boiling point of the feed was 190°C, with 10 wt% of the VGO feed boiling by 366°C, 30 wt% of the VGO feed boiling by 424°C, 50 wt% of the VGO feed boiling by 462°C, 70 wt% of the VGO feed boiling by 500°C, and 90 wt% of the VGO feed boiling by 480°C. The final boiling point was 580°C.

[0105] A pilot plant with two reactors connected in series was used for the hydrocracking process. Two sets of experiments were performed: (1) with a large crystallite size zeolite catalyst (catalyst composition 2); (2) with a conventional size catalyst (catalyst composition 1). The first reactor was loaded with 112.5 ml of a commercial pre-treated catalyst, which is an amorphous silica-alumina catalyst with Ni and W as active phase metals, followed by 112.5 ml of catalyst composition 1. The second reactor was loaded with a commercial hydrocracking catalyst comprising 15 wt. % zeolite and 85 wt. % silica-alumina containing catalyst with Ni and W as active phase metals. The pilot plant was fed with 1263 Nm of hydrogen. 3 / m 3The reaction using catalyst composition 1 in the first reactor was carried out in succession without cooling during the temperature increase. 361.6°C and 370.9°C and in a second reactor, the reaction was carried out using a commercial hydrocracking catalyst comprising 15 wt. % zeolite and 85 wt. % silica-alumina containing catalyst with Ni and W as active phase metals. 351.5°C and 359.0°C In run 2, the first reactor was loaded with 112.5 ml of a commercial pretreated catalyst, which was an amorphous silica-alumina catalyst with Ni and W as active phase metals, followed by 112.5 ml of catalyst composition 2. The second reactor was loaded with a commercial hydrocracking catalyst comprising 15 wt. % zeolite and 85 wt. % silica-alumina containing catalyst with Ni and W as active phase metals. The pilot plant was fed with 1263 Nm of hydrogen. 3 / m 3 The reaction using catalyst composition 2 in the first reactor was carried out in succession without cooling during the temperature increase. 360.8°C, 371.1°C, and 381.3°C and in the second reactor, a reaction using a commercial hydrocracking catalyst was carried out. 350.6°C, 359.7°C, and 370.1°C So I went.

[0106] A chart of VGO feed conversion versus reactor temperature is provided in Figure 6, and the data is summarized in Table 2. As shown in Figure 6, catalyst composition 2, which includes large crystal USY ("15 μm") zeolite, has a higher conversion at the same temperature than catalyst composition 1, which includes conventional sized USY ("2 μm") zeolite. Thus, catalyst composition 2 is more active than catalyst composition 1.

[0107] [Table 2]

[0108] A chart of middle distillate (MD) and naphtha selectivity versus VGO feed conversion is provided in Figure 7, and the data is summarized in Table 3. As shown in Figure 7, catalyst composition 2, which includes large crystal USY ("15 μm") zeolite, is more selective to naphtha at the conversions studied than catalyst composition 1, which includes conventionally sized USY ("2 μm") zeolite. Conversely, catalyst composition 2 is less selective for middle distillates than catalyst composition 1.

[0109] [Table 3]

[0110] It should be noted that statements in this disclosure that components of the disclosure are "operable" or "sufficient" to embody certain properties or to function in a certain manner are structural statements, as opposed to statements of intended use. More specifically, references in this disclosure to how a component is "operable" or "sufficient" refer to the existing physical state of the component and should therefore be construed as definitive statements of the structural features of the component.

[0111] Although the subject matter of the present disclosure has been described in detail and with reference to specific embodiments, it should be noted that various details disclosed in the present disclosure should not be construed as implying that these details relate to elements that are essential constituents of the various embodiments described in the present disclosure. Moreover, it will be apparent that modifications and variations are possible without departing from the scope of the present invention, including, but not limited to, the embodiments defined in the appended claims.

[0112] Nouns include plural referents unless otherwise specified.

[0113] Throughout this disclosure, ranges are provided. Each discrete value encompassed by the range is also envisioned. Furthermore, ranges that may be formed by each discrete value encompassed in an expressly disclosed range are likewise envisioned.

[0114] As used in this disclosure and the appended claims, the terms "comprise," "have," and "include," as well as all grammatical variations thereof, are each intended to have an open, non-limiting meaning that does not exclude additional elements or steps.

[0115] As used in this disclosure, terms such as "first" and "second" are assigned arbitrarily and are intended merely to distinguish between two or more instances or components. It should be understood that the words "first" and "second" serve no other purpose, are not part of the name or description of the components, and do not necessarily define the relative location, position, or order of the components. Furthermore, it should be understood that the mere use of the terms "first" and "second" does not require that an optional "third" component be present, although that possibility is contemplated within the scope of this disclosure. Preferred embodiments of the present invention will be described below in detail. EMBODIMENT 1 1. A catalyst composition comprising: at least one hydrogenation metal component, and Carrier, Including, the support comprises a framework-substituted ultrastable Y (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms; A catalytic composition, wherein the framework substituted USY zeolite has an average crystallite size of from 5 μm to 50 μm. EMBODIMENT 2 2. The catalyst composition according to embodiment 1, wherein the framework-substituted ultrastable Y-zeolite is substituted with 0.1 to 5% by weight, calculated on an oxide basis, of zirconium atoms, or with 0.1 to 5% by weight, calculated on an oxide basis, of titanium atoms, or with 0.1 to 5% by weight, calculated on an oxide basis, of zirconium atoms and 0.1 to 5% by weight, calculated on an oxide basis, of titanium atoms. EMBODIMENT 3 3. The catalyst composition of embodiment 1 or 2, wherein the framework-substituted ultrastable Y-type zeolite comprises hafnium atoms. EMBODIMENT 4 4. The catalyst composition of any one of embodiments 1 to 3, further comprising an inorganic oxide compound selected from alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, and combinations of two or more thereof. EMBODIMENT 5 5. The catalyst composition of any one of embodiments 1 to 4, wherein the at least one hydrogenation metal component comprises 0.01% to 40% by weight of the catalyst composition. EMBODIMENT 6 The framework-substituted ultrastable Y-type zeolite has a crystal lattice constant of 2.42 nm to 2.45 nm, a crystal lattice constant of 600 nm 2 / g to 900m 2 / g, and 5 to 100 SiO 2 Against Al 2 O3 6. The catalyst composition of any one of the preceding embodiments, having a molar ratio of: EMBODIMENT 7 The catalyst composition is 200 m 2 / g to 450m 2 7. The catalyst composition of any one of the preceding claims, having a specific surface area of ​​0.1 to 0.75 ml / g and a plurality of pores with a diameter of 600 Å or less, the pores having a volume of 0.4 ml / g to 0.75 ml / g. EMBODIMENT 8 8. The catalyst composition of any one of the preceding embodiments, wherein the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof. EMBODIMENT 9 9. The catalyst composition of any one of the preceding embodiments, further comprising an inorganic oxide compound selected from the group consisting of alumina, silica, and mixtures of alumina and silica, and wherein the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof. EMBODIMENT 10 1. A method for producing a catalyst composition comprising the steps of: forming an ultrastable Y-type (USY) zeolite having an average crystallite size of 5 μm to 50 μm; heating the USY zeolite at a temperature of 500° C. to 700° C.; forming a suspension comprising said USY zeolite and having a liquid / solid ratio of from 5 to 15; adding at least one inorganic acid, at least one organic acid, or a mixture of at least one inorganic acid and at least one organic acid to the suspension such that the pH of the suspension is equal to or less than 2; mixing a zirconium compound, a titanium compound, a hafnium compound, or a mixture of two or more thereof with said suspension having a pH of 2 or less; and adding a base to the suspension to a pH of 6 to 8 to provide a framework substituted USY zeolite; The method includes: EMBODIMENT 11 The ultrastable Y-type zeolite has a crystal lattice constant of 2.42 nm to 2.45 nm and a crystal lattice constant of 600 nm. 2 / g to 900m 2 / g, and 5 to 100 SiO 2 Against Al 2 O 3 11. The method of embodiment 10, wherein the molar ratio of EMBODIMENT 12 12. The method of claim 10 or 11, further comprising adding at least one hydrogenation metal component to the catalyst composition, wherein the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof. EMBODIMENT 13 A method for hydrocracking a hydrocarbon oil, comprising the steps of: contacting the hydrocarbon oil with at least one catalytic composition and hydrogen in a reactor to hydrocrack the hydrocarbon oil; Including, The catalyst composition comprises: at least one hydrogenation metal component, and Carrier, Including, the support comprises a framework-substituted ultrastable Y (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms; The framework substituted USY zeolite has an average crystallite size of 5 μm to 50 μm. EMBODIMENT 14 14. The process of embodiment 13, wherein the hydrocracking is carried out at a temperature of from 300° C. to 500° C. EMBODIMENT 15 The reactor is a continuous flow reactor, the hydrocarbon oil has a boiling point of 375°C to 833°C, the hydrogen is added to the reactor at a pressure of 3.5MPa to 25MPa, the reactor has a liquid hourly space velocity of 0.1 to 10 hours, and the reactor is heated to 500Nm 3 / m 3 from 2500Nm 3 / m 3 15. The method of embodiment 13 or 14, wherein the hydrogen / oil ratio is EMBODIMENT 16 14. The method of embodiment 13, further comprising collecting a distillate from the reactor.

Claims

1. A catalyst composition for hydrocracking a hydrocarbon oil, comprising: at least one hydrogenation metal component, and Carrier, Including, the support comprises a framework-substituted ultrastable Y (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms; A catalytic composition, wherein the framework substituted USY zeolite has an average crystallite size of 11 μm to 50 μm.

2. 2. The catalyst composition of claim 1, wherein the framework-substituted ultrastable Y-zeolite is substituted with 0.1 to 5% by weight of zirconium atoms, calculated on an oxide basis, or with 0.1 to 5% by weight of titanium atoms, calculated on an oxide basis, or with 0.1 to 5% by weight of zirconium atoms, calculated on an oxide basis, and 0.1 to 5% by weight of titanium atoms, calculated on an oxide basis.

3. 3. The catalyst composition of claim 1 or 2, wherein the framework-substituted ultrastable Y-zeolite contains hafnium atoms.

4. 3. The catalyst composition of claim 1 or 2, further comprising an inorganic oxide compound, the inorganic oxide compound comprising alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, and combinations of two or more thereof.

5. 3. The catalyst composition of claim 1 or 2, wherein said at least one hydrogenation metal component comprises from 0.01 wt.% to 40 wt.% of said catalyst composition.

6. The framework-substituted ultrastable Y-type zeolite has a crystal lattice constant of 2.42 nm to 2.45 nm, 2 / g to 900m 2 / g specific surface area and 5 to 100 SiO 2 Against Al 2 O 3 3. The catalyst composition of claim 1, wherein the molar ratio of

7. The catalyst composition is 200 m 2 / g to 450m 2 3. The catalyst composition according to claim 1, having a specific surface area of ​​0.1 to 1.0 nm / g and a plurality of pores with a diameter of 600 Å or less, the pores having a volume of 0.4 ml / g to 0.75 ml / g.

8. 3. The catalyst composition of claim 1 or 2, wherein the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

9. 3. The catalyst composition of claim 1 or 2, further comprising an inorganic oxide compound selected from the group consisting of alumina, silica, and mixtures of alumina and silica, and wherein the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

10. A method for producing a catalyst composition for hydrocracking a hydrocarbon oil, comprising the steps of: forming an ultrastable Y-type (USY) zeolite having an average crystallite size of 11 μm to 50 μm; heating the USY zeolite at a temperature of 500° C. to 700° C.; forming a suspension comprising said USY zeolite and having a liquid / solid ratio of from 5 to 15; adding at least one inorganic acid, at least one organic acid, or a mixture of at least one inorganic acid and at least one organic acid to the suspension such that the pH of the suspension is equal to or less than 2; mixing a zirconium compound, a titanium compound, a hafnium compound, or a mixture of two or more thereof with said suspension having a pH of 2 or less; and adding a base to the suspension to a pH of 6 to 8 to provide a framework-substituted USY zeolite; The method includes:

11. The ultrastable Y-type zeolite has a crystal lattice constant of 2.42 nm to 2.45 nm and a crystal lattice constant of 600 nm. 2 / g to 900m 2 / g specific surface area and 5 to 100 SiO 2 Against Al 2 O 3 The method of claim 10, wherein the molar ratio is:

12. 12. The method of claim 10 or 11, further comprising the step of adding at least one hydrogenation metal component to the catalyst composition, wherein the at least one hydrogenation metal component is selected from the group consisting of iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, tungsten, and combinations of two or more thereof.

13. A method for hydrocracking a hydrocarbon oil, comprising the steps of: contacting the hydrocarbon oil with at least one catalytic composition and hydrogen in a reactor to hydrocrack the hydrocarbon oil; Including, The catalyst composition comprises: at least one hydrogenation metal component, and Carrier, Including, the support comprises a framework-substituted ultrastable Y (USY) zeolite substituted with zirconium atoms, titanium atoms, or both zirconium and titanium atoms; The framework substituted USY zeolite has an average crystallite size of 11 μm to 50 μm.

14. The process of claim 13, wherein the hydrocracking is carried out at a temperature of from 300° C. to 500° C.

15. The reactor is a continuous flow reactor, the hydrocarbon oil has a boiling point of 375° C. to 833° C., the hydrogen is added to the reactor at a pressure of 3.5 MPa to 25 MPa, the reactor has a liquid hourly space velocity of 0.1 to 10 hours, and the reactor is operated at a pressure of 500 Nm 3 / m 3 From 2500 Nm 3 / m 3 15. The process of claim 13 or 14, wherein the hydrogen / oil ratio is

16. The method of claim 13 further comprising the step of collecting a distillate from the reactor.

Citation Information

Patent Citations

  • Information recording and reproducing device

    JP1993036099A

  • Hydrocarbon oil hydrocracking catalyst, hydrocracking catalyst production method, and method for hydrocracking hydrocarbon oil using hydrocracking catalyst

    JP2017006921A

  • Zirconia-containing catalysts

    US4255288A